To complete the polynomial equation showing the subtraction of the second expression from the first, we start with the given expression:
The first expression is: \[ 9x^2 + x + 13 \]
The second expression is: \[ 2x^2 + 12x + x^2 + 5x + 2 \]
First, we combine like terms in the second expression: \[ 2x^2 + x^2 = 3x^2 \] \[ 12x + 5x = 17x \]
So, the second expression simplifies to: \[ 3x^2 + 17x + 2 \]
Now we write the subtraction: \[ (9x^2 + x + 13) - (3x^2 + 17x + 2) \]
This results in:
-
Subtract the \(x^2\) terms: \[ 9x^2 - 3x^2 = 6x^2 \]
-
Subtract the \(x\) terms: \[ x - 17x = -16x \]
-
Subtract the constant terms: \[ 13 - 2 = 11 \]
Putting it all together, the final expression after the subtraction is: \[ 6x^2 - 16x + 11 \]
Thus, the completed polynomial equation is: \[ 9x^2 + x + 13 - (3x^2 + 17x + 2) = 6x^2 - 16x + 11 \]